2015
DOI: 10.1002/pola.27771
|View full text |Cite
|
Sign up to set email alerts
|

High solids TEMPO‐mediated radical semibatch emulsion polymerization of styrene

Abstract: A bicomponent initiation system consisting of 2,2,6,6‐tetramethylpiperidine‐N‐oxyl (TEMPO) and the water soluble initiator potassium persulfate (KPS) was used to develop a robust and versatile semibatch emulsion polymerization process to obtain polystyrene (PS) latexes with solids contents of 5–40 wt %. A window of operating conditions was found that yielded high conversion (>95%) stable latexes and well controlled polymers, overcoming limitations found in previous attempts at developing similar processes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 60 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…For example, for the system TEMPO/KPS, at the beginning of the reaction, a high fraction of TEMPO is solubilized in the organic phase [31] (micelles or droplets), while most of the KPS resides in the aqueous phase. [32,33] In a previous report for the emulsion NMRP of St using the TEMPO/KPS system, [25] the polymerization was successful because the nitroxide was kept primarily inside the particles from the beginning of the reaction due to its relatively high hydrophobicity. By remaining inside the particles, the nitroxide controlled the growth of the polymer chains in the particle phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for the system TEMPO/KPS, at the beginning of the reaction, a high fraction of TEMPO is solubilized in the organic phase [31] (micelles or droplets), while most of the KPS resides in the aqueous phase. [32,33] In a previous report for the emulsion NMRP of St using the TEMPO/KPS system, [25] the polymerization was successful because the nitroxide was kept primarily inside the particles from the beginning of the reaction due to its relatively high hydrophobicity. By remaining inside the particles, the nitroxide controlled the growth of the polymer chains in the particle phase.…”
Section: Resultsmentioning
confidence: 99%
“…After this work, many reports by ab initio, [12,17] stepwise, [16,18,19] seeded, [11,[18][19][20][21][22][23] and semibatch [19,24,25] emulsion polymerization processes appeared, using different nitroxides such as hydroxy-TEMPO, [12,20,21] amino-TEMPO, [12] TEMPO, [11][12][13][14][19][20][21]25] N-tert-butyl-N-(1-diethylphosphono-2,2-dimethylpropyl)-N-oxyl (SG1), [15] and the alkoxyamines BlocBuilder (BB) [16][17][18]22,24,26] and DiBlocBuilder (DiBB). [23,24] However, the majority of these processes presented some problems and drawbacks such as long seed-formation and…”
Section: Doi: 101002/mren202000054mentioning
confidence: 99%
“…A robust semicontinuous emulsion polymerization process has been developed by our group . During its development it was found that the critical process variables to simultaneously reach latex stability and control, main challenge in true emulsion NMP processes, were the surfactant concentration, the initial monomer concentration (and its ratio to nitroxide) present during the nucleation period and early stages of the emulsion before the start of the semicontinuous feed of monomer, and the monomer feed rate.…”
Section: A Robust Semicontinuous Emulsion Polymerization Processmentioning
confidence: 99%
“…The development of NMP processes in emulsion polymerization has been a goal pursued by several research groups during the last 10–15 years; only some of the attempts have reached some level of success. Our group recently presented a robust and versatile semibatch NMP emulsion polymerization process which is simple to perform, produces a long‐term (months) stable latex at high monomer conversions in reasonable reaction times (8 h), and can be run with solids contents of up to 40 %, which is the highest level so far reported in the literature. The process can be implemented using an alkoxyamine as initiator (monomolecular process) or a pair of nitroxide radical and a conventional radical initiator (bimolecular process).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation